Tantangan dan Problematika Pendidikan Masa Kini dalam Perspektif Islam di Era Globalisasi - Abdul Azis; Ahmad Fadli Rizqi; Lusiani Lestiana Indah; Najwa Khayla K (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study examines the challenges and problems faced by Islamic education amid the complex dynamics of globalization. While globalization brings positive impacts through advances in information and communication technology, it also poses challenges such as the infiltration of global cultural values that do not always align with Islamic principles. This study employs a descriptive qualitative approach using a library research method, drawing from scholarly sources in national journals and recent academic books. The findings reveal that Islamic education encounters internal challenges such as conventional teaching methods, curricula that are unresponsive to changing times, and low digital literacy among educators. Meanwhile, external challenges include the secularization of education, unequal access, technological revolutions, and multicultural issues. To address these challenges, it is necessary to reformulate an integrative curriculum, improve teacher professionalism, and create educational environments that support Islamic values. This article recommends a transformative and adaptive approach to Islamic education that remains firmly rooted in the values of tawhid and akhlaq al-karimah in facing global challenges.